STAR-GARCH Models for Stock Market Interactions in the Pacific Basin Region, Japan and US - Giorgio Busetti; Matteo Manera (Fondazione Eni Enrico Mattei (FEEM), 2003)
We investigate the financial interactions between countries in the Pacific Basin region (Korea, Singapore, Malaysia, Hong Kong and Taiwan), Japan and US. The originality of the paper is the use of STAR-GARCH models, instead of standard correlation-cointegration techniques. For each country in the Pacific Basin region, we find statistically adequate STAR-GARCH models for the series of stock market daily returns, using Nikkei225 and S&P500 as alternative threshold variables. We provide evidence for the leading role of Japan in the period 1988-1990 (pre-Japanese crisis years), whereas our results suggest that the Pacific Basin region countries are more closely linked with the US during the period 1995-1999 (post- Japanese crisis years).
Keywords: C22; C51; C52; F36; 330; STAR-GARCH models; stock market integration; Pacific-Basin capital markets; outliers; Aktienmarkt; Preiskonvergenz; ARCH-Modell; Ostasien; Japan; USA; Autokorrelation